Case Report: Composite pheochromocytoma with ganglioneuroma component: A report of three cases - Araujo, Paula B.; Carvallo, Mirna S.; Vidal, Ana P.; Nascimento, João B.; Wo, Julia M.; Naliato, Erika O.; Cunha Neto, Silvio H.; Conceição, Flavia L.; Fontes, Rosita; de Lima, Vinicius V.; Carvalho, Denise P.; Soares, Paula; et al. (Frontiers in Endocrinology, 2022)
Composite pheochromocytoma (CP) is a very rare tumor originating from neural crest cells predominantly composed of pheochromocytoma (PCC), a chromaffin cell tumor arising in adrenal medulla, and ganglioneuroma, a tumor derived of autonomic ganglion cells of nervous system. Moreover, CP may be present in the hereditary syndromes of which pheochromocytoma is part. Literature offers scarce data on this subject, and particularly about its biological behavior, clinical evolution, and molecular profile. We reported the phenotype and outcome of three cases of CP (PCC and ganglioneuroma components), followed at the Endocrine Service of the Clementino Fraga Filho University Hospital, Federal University of Rio de Janeiro, UFRJ, Rio de Janeiro, Brazil. Two non-syndromic patients were negative to germline mutations in genes VHL, SDHB, SDHC, SDHD, SDHAF2, TMEM127, and MAX while the third case had clinical diagnosis of neurofibromatosis syndrome. The mean age at the diagnosis of three cases was 38.33 ± 9.01 years with mean follow-up time of 9.33 ± 7.09 years. All cases had apparent symptoms of catecholaminergic excess secreted by PCC. Ganglioneuroma, the neurogenic component present in all three cases, had a percentage representation ranging from 5 to 15%. Tumors were large (6-7.5 cm) and unilateral tumors. All cases underwent adrenalectomy with no recurrence or metastasis or development of contralateral tumor during follow-up. Genetic testing has been scarcely offered to CP cases. However, a similar frequency of genetic background is found when compared with classic PCC, mainly by overrepresentation of NF1 cases in CP subset. By literature review, there was a significant increase of cases reported with CP in the last decade indicating a recent improvement of the diagnosis of this rare disorder in clinical practice.